Electromediated Aldol Reaction in EtOH/H2O. Issue 7 (1st July 2022) - Zhang, Mengxun; Du, Yi; Huang, Liping; Zhu, Qinchang; Li, Chenyang; He, Zhendan
Abstract : An environment-friendly electromediated aldol reaction is reported here. With KI as mediator, ketones and aldehydes could be readily converted into β -hydroxyl ketones in EtOH/H2 O. A variety of functionalities were compatible with this safe and green method. Mechanism of this transformation was explored with control experiments and cyclic voltammetry.